Ralf Dahrendorf Denker, Politiker, Publizist - Hauser, Thomas (W. Kohlhammer GmbH, 2019)
Democratic institutions are currently facing a crisis of legitimacy, and the political system is also coming under pressure along with them. It is therefore high time to engage with the liberal thinker Ralf Dahrendorf, who was already describing the basic elements of this crisis as long ago as the 1980s. As a brilliant wanderer between different fields and disciplines, he not only commuted between the Anglo-Saxon and European worlds, but was also equally active as a journalist, academic and politician. Drawing on his countless writings, Thomas Hauser portrays in a lively and insightful way the basic aspects of this great intellectual=s thinking, which can still help us to grasp complex developments in today=s global world. Die demokratischen Institutionen stecken derzeit in einer Legitimationskrise. Und mit ihnen ist auch das politische System unter Druck geraten. Höchste Zeit sich mit dem liberalen Denker Ralf Dahrendorf zu beschäftigen, der bereits in den 1980er-Jahren die Grundelemente dieser Krise beschrieben hat. Als genialer Grenzgänger war er nicht nur Pendler zwischen der angelsächsischen und der europäischen Welt, sondern er war gleichermaßen als Journalist, Wissenschaftler und Politiker tätig. Aus seinen unzähligen Schriften zeichnet Thomas Hauser präzise und profund die Grundzüge des Denkens dieses großen Intellektuellen nach, die uns noch heute helfen können, die komplexen Entwicklungen einer globalen Welt besser zu verstehen